2001
DOI: 10.1111/j.1365-2621.2001.tb16117.x
|View full text |Cite
|
Sign up to set email alerts
|

Chilled Storage of Pressurized Octopus (Octopus vulgaris) Muscle

Abstract: Samples were subjected to continuous and step-pulsed pressurization, in both cases at 7 and 40 ЊC. There was a reduction of microbial flora (total viable count and lactic bacteria) after pressurization and during storage at 2.5 to 3.0 ЊC, chiefly in the lot pressurized by step-pulse at 400 MPa, 40 ЊC. Pressure-induced modification of the microbial flora resulted in a lower level of nitrogenous compounds. Pressurization reduced autolytic activity, but shear strength values remained stable throughout storage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 39 publications
6
39
0
Order By: Relevance
“…Vaz Pires et al (2008) stated that the autolytic activity of endogenous enzymes rather than microbial enzymes was mainly responsible for the changes in sensory attributes. Hurtado et al (2001) however observed no change in the autolytic activity values of untreated and pressurized octopus muscle during chilled storage (3°C) and attributed that pressurization at 400 MPa had inhibited the activity of muscle proteases.…”
Section: Biochemical Qualitymentioning
confidence: 96%
See 2 more Smart Citations
“…Vaz Pires et al (2008) stated that the autolytic activity of endogenous enzymes rather than microbial enzymes was mainly responsible for the changes in sensory attributes. Hurtado et al (2001) however observed no change in the autolytic activity values of untreated and pressurized octopus muscle during chilled storage (3°C) and attributed that pressurization at 400 MPa had inhibited the activity of muscle proteases.…”
Section: Biochemical Qualitymentioning
confidence: 96%
“…Autolytic activity Autolytic activity of the octopus muscle was determined by the method of Hurtado et al (2001). The octopus muscle homogenate was mixed with five volumes of chilled 0.15 M NaCl and filtered through the moist gauze.…”
Section: Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of 1-3 days in the shelf life between the octopus species is probably due to the mean temperature of storage, the criteria of the freshness scale, or the intrinsic properties of the species (Ashie et al 1996;Dalgaard, 2000). There are major differences between O. maya and O. vulgaris, in particular Hurtado et al (2001) for O. vulgaris (10 4 CFU/g). Since bacterial concentrations are higher in shallow waters than in deeper waters, the octopus comes ashore with a high intrinsic bacterial concentration (Sieburth, 1971).…”
Section: Sensory Quality Datamentioning
confidence: 99%
“…In their trail, the authors found that the rejection of octopus kept in crushed ice occurs at day 8. Several attempts were carried out to increase the shelf life by an appropriate treatment (high pressure, heat combined to high pressure, gamma radiation) and to improve the textural properties inducing the softening of meat (Hurtado et al, 2001a(Hurtado et al, , 2001b(Hurtado et al, , 2001cSinanoglou et al, 2007). Recently, Mendes et al (2011) tested the active packaging based on soluble CO2 stabilisation (SGS) methodology to obtain readyto-eat products.…”
Section: Qualitymentioning
confidence: 99%